2012
DOI: 10.1590/s0101-20612012005000064
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in yacon products and effect of long term storage

Abstract: Yacon (Smallanthus sonchifolius (Poepp. and Endl.) H. Robinson) is a storage root originally grown in the Andean highlands. The fresh roots are perishable and quickly turn brown during handling and processing. Aiming to prolong shelf-life and to preserve the antioxidant compounds in yacon roots, 3 mm thick yacon slices were dried in a drying cabinet at 40, 50, and 60 ºC to a moisture content of 10-14%, and yacon strips were sun dried to a moisture content of 15-20%. The total phenolic content was measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
2
18
0
4
Order By: Relevance
“…), oven and solar drying (Castro et al . ), heat pump drying (Shi et al . ), osmo‐convective technique (Perussello et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), oven and solar drying (Castro et al . ), heat pump drying (Shi et al . ), osmo‐convective technique (Perussello et al .…”
Section: Introductionmentioning
confidence: 99%
“…Powdered yacon was obtained from convective drying both the pulp encapsulated by native starch (Lago et al 2012) and the fresh roots (Vasconcelos et al 2010). The most common procedure is to dehydrate the sliced tuberous part by several technologies: osmotic dehydration in sucrose solution (Maldonado et al 2008), vacuum oven drying (Reis et al 2012), oven and solar drying (Castro et al 2012), heat pump drying (Shi et al 2013), osmo-convective technique (Perussello et al 2014) and convection followed by lyophilization (Bernstein and Noreña 2014). Despite the various techniques reported, there are no publications on the use of foam mat drying (FMD) for the purpose discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that yacon also presents antioxidant activity related to compounds such as flavonoids (Arnao et al 2011), phenolic acids (Castro et al 2012), and tryptophan (Yan et al 1999), beyond anti-inflammatory (Honoré et al 2012), anti-obesity (Hasani-Ranjbar et al 2013), antibacterial (Joung et al 2010), antifungal (Yun et al 2012), and anticancer (Moura et al 2012) activities.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this study provides the first clinical evidence that six weeks of yacon flour consumption reduces oxidative stress status in adults with excess body weight. Yacon is a source of phenolic compounds (658 mg GAE/100g of flour), mainly chlorogenic acid, that could neutralize free radicals and improve oxidative stress (3,4,7,27). These compounds contain hydroxyl groups, which can donate electrons and thus reduce free radicals' production, avoiding biomolecules oxidation (10).…”
Section: Discussionmentioning
confidence: 99%